Timed artificial insemination programs during the summer in lactating dairy cows: Comparison of the 5-d Cosynch protocol with an estrogen/progesterone-based protocol - Pereira, M. H C; Rodrigues, A. D P; Martins, T.; Oliveira, W. V C; Silveira, P. S A; Wiltbank, M. C.; Vasconcelos, J. L M (American Dairy Science Association, 2013)
The objective of this study was to compare a GnRH-based to an estrogen/progesterone (E2/P4)-based protocol for estrous cycle synchronization and fixed timed artificial insemination (TAI), both designed for synchronization of ovulation and to reduce the period from follicular emergence until ovulation in cows with a synchronized follicular wave. A total of 1,190 lactating Holstein cows (primiparous: n = 685 and multiparous: n = 505) yielding 26.5 ± 0.30 kg of milk/d at 177 ± 5.02 d in milk were randomly assigned to receive one of the following programs: 5-d Cosynch protocol [d -8: controlled internal drug release (CIDR) + GnRH; d -3: CIDR removal + PGF2α; d -2: PGF2α; d 0: TAI + GnRH] or E2/P4 protocol (d -10: CIDR + estradiol benzoate; d -3: PGF2α; d -2: CIDR removal + estradiol cypionate; d 0: TAI). Rectal temperature and circulating progesterone (P4) were measured on d -3, -2, 0 (TAI), and 7. The estrous cycle was considered to be synchronized when P4 was ≥1.0 ng/mL on d 7 in cows that had luteolysis (P4 ≤0.4 ng/mL on d 0). To evaluate the effects of heat stress, cows were classified by number of heat stress events: 0, 1, and 2-or-more measurements of elevated body temperature (≥39.1°C). Pregnancy success (pregnancy per artificial insemination, P/AI) was determined at d 32 and 60 after TAI. The cows in the 5-d Cosynch protocol had increased circulating P4 at the time of PGF2α injection (2.66 ± 0.13 vs. 1.66 ± 0.13 ng/mL). The cows in the E2/P4 protocol were more likely to be detected in estrus (62.8 vs. 43.4%) compared with the cows in the 5-d Cosynch protocol, and expression of estrus improved P/AI in both treatments. The cows in the 5-d Cosynch protocol had greater percentage of synchronized estrous cycle (78.2%), compared with cows in the E2/P4 protocol (70.7%). On d 60, the E2/P4 protocol tended to improve P/AI (20.7 vs. 16.7%) and reduced pregnancy loss from 32 to 60 d (11.0 vs. 19.6%), compared with the 5-d Cosynch protocol. In cows with their estrous cycle synchronized, the E2/P4 protocol had greater P/AI (25.6 vs. 17.7%) on d 60 and lower pregnancy loss from 32 to 60 d (6.7 vs. 21.7%) compared with cows in the 5-d Cosynch protocol. Follicle diameter affected pregnancy loss from 32 to 60 d only in the cows in the 5-d Cosynch protocol, with smaller follicles resulting in greater pregnancy loss. Pregnancy per AI at d 60 was different between protocols in the cows with 2 or more measurements of heat stress (5-d Cosynch = 12.2% vs. E2/P4 = 22.8%), but not in the cows without or with 1 heat stress measurement. In conclusion, the 5-d Cosynch protocol apparently produced better estrous cycle synchronization than the E2/P4 protocol but did not improve P/AI. The potential explanation for these results is that increased E2 concentrations during the periovulatory period can improve pregnancy success and pregnancy maintenance, and this effect appears to be greatest in heat-stressed cows when circulating E2 may be reduced. © 2013 American Dairy Science Association.
Keywords: 5-d Cosynch; dairy cow; estrogen/progesterone protocol; fertility